Estimación de una ecuación explícita derivada de un Nomograma, para el cálculo del tirante normal de un canal Rectangular y evaluación de su grado de interrelación mediante hoja de cálculo de Excel - Rodriguez Aguirre, Jhon Edgar (2017)
In agricultural engineering when evaluating the normal strap of a rectangle channel requires the use of numerical methods to solve the real problems that arise. This is why it was necessary to create an explicit method and implement it to an Excel spreadsheet for quick execution. On the basis of this we propose to estimate six explicit equations based on the nomogram of curves to determine the normal depth of Ven Te Chow, for the calculation of the normal rod of a rectangle channel. The curve corresponding to the normal rod for rectangle channels of the Ven Te Chow nomogram will be digitized with the help of the AutoCAD program. We will thus obtain a vectorized entity of the curve to which we will simultaneously break to obtain a representative number of vertices from which we can extract its coordinates, which will be in a linear scale, then we will generate a database which will be converted to logarithmic scale, We divided this group of data into six logarithmic quadrants and proceeded to perform the polynomial regressions that would give us the six explicit equations to calculate the normal rod of a rectangle channel. The six explicit explicit equations give us very significant results for channels with 0.45 meters of maximum normal strut, for larger normal struts it is advisable to apply a correction value.